Correlation of β2-microglobulin with postoperative delirium and 3-year mortality undergoing knee or hip replacement surgery: a prospective cohort study - Wang, Yuanlong; He, Qian; Fu, Kun; Bi, Yanlin; Wang, Bin; Kong, Wenjie; Hua, Shuhui; Kong, Jian; Xu, Shanling; Gong, Hongyan; Wang, Jiahan; Li, Chuan; et al. (Frontiers in Medicine, 2025)
IntroductionPostoperative delirium (POD) is a commonly occurring condition in the postoperative period. Therefore, the study intends to investigate the relationship between B2M and POD and the effect of B2M levels on three-year postoperative mortality in patients with POD.MethodsPostoperatively, the Confusion Assessment Method (CAM) and the Monumental Delirium Assessment Scale (MDAS) were used to assess the incidence and severity of POD. Preoperative plasma B2M levels were measured utilizing a latex-enhanced immunoturbidimetric assay. Total tau protein (T-tau), phosphorylated tau protein (P-tau), and amyloid β plaque 42 (Aβ42) were detected in preoperative cerebrospinal fluid (CSF) by enzyme-linked immunosorbent assay. Logistic regression equations were applied to examine the risk factors linked to POD. Patients presenting with POD were grouped according to B2M level and followed up for 3 years postoperatively for their survival and Kaplan–Meier survival curves were plotted.ResultsThe prevalence of POD was 7.23%. Serum B2M levels were higher in POD patients compared to non-POD (NPOD) patients (p = 0.01). The results of the logistic regression analysis indicated that B2M (OR = 1.394, 95% CI = 1.017–1.910, p = 0.002) and T-tau (OR = 1.006, 95% CI = 1.002–1.011, p = 0.007) posed a risk for POD. B2M and POD were partially associated through the mediation of CSF T-tau (10.0%). The K-M survival curves showed that patients with high B2M who developed POD had a higher mortality rate 3 years after surgery (p = 0.031).ConclusionIn summary, B2M may be a risk factor for POD, which might be mediated in part by CSF T-tau.